2012
DOI: 10.1159/000338509
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Production Stimulated by CD14+Monocytes-paracrined IL-1ß does not Contribute to the Immunosuppressive Activity of Human Umbilical Cord Mesenchymal Stem Cells

Abstract: Background/Aims: Human umbilical cord mesenchymal stem cells (hUC-MSCs) possess immunosuppressive activities but the mechanisms of such activities are not fully understood. Here, we investigated the role of IL-6, one of the characteristic factors of MSCs, in the immunoregulating effect of hUC-MSCs on CD4+ T lymphocytes. Methods: The condition media from human peripheral blood mononuclear cells (hPBMCs) or CD14+/- cell were tested if stimulating IL-6 production by hUC-MSCs. The related signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…IL-6, in conjunction with TGF-b, regulates the Th17/T regulatory balance [28,29] but blocking IL-6 does not restore human lymphocyte proliferation [30]. Similar to findings in other species, we found little to no impact of IL-6 on T cell proliferation, demonstrating that it is neither necessary nor sufficient for MSC-based inhibition of T cell proliferation in vitro.…”
Section: Figsupporting
confidence: 54%
“…IL-6, in conjunction with TGF-b, regulates the Th17/T regulatory balance [28,29] but blocking IL-6 does not restore human lymphocyte proliferation [30]. Similar to findings in other species, we found little to no impact of IL-6 on T cell proliferation, demonstrating that it is neither necessary nor sufficient for MSC-based inhibition of T cell proliferation in vitro.…”
Section: Figsupporting
confidence: 54%
“…We also found that IL-1β promoted the secretion of IL-6 by UC-MSC via JNK and NF-κB signaling pathway. However IL-6 is not directly associated with the immunoinhibitory activity UC-MSC on CD4 + T cell [39]. IL-6 was originally isolated and cloned as a B-cell differentiation factor that induced terminal B-cell differentiation and supported the production of immunoglobulin G (IgG) [40,41] We observed that although the level of IL-6 was higher in coculture system, the neutralizing antibodies to IL-6 did not affect the immunomodulation on B cells.…”
Section: Discussionmentioning
confidence: 89%
“…This dose-response curve was similar to the curve obtained for IL-1ß stimulation. When combined with IFN-γ (50 ng/ml (3 nM), a concentration measured when PBMCs were stimulated by phytohemagglutinin [ 8 10 ]), TNF-α induced increased IL-6 production along a hyperbolic relationship (r 2 = 0.95). Interestingly, the half-maximal stimulation was increased and reached at 0.7 ng/ml TNF-α (0.044±0.019 nM, mean±SEM).…”
Section: Resultsmentioning
confidence: 99%
“…MCP-1 may play a direct role in anti-inflammation [ 18 , 19 ] but mainly mobilizes the partners involved in this communication [ 14 , 20 ]. We have previously reported that IL-1α in part, but essentially IL-1ß (both autocrine and paracrine), as produced by both hUC-MSCs and PBMCs, are the main regulators of IL-6 production by hUC-MSCs [ 8 10 ]. Here, we showed that TNF-α production was itself controlled by IL-1ß at the level of PBMCs.…”
Section: Discussionmentioning
confidence: 99%